2015
DOI: 10.1017/ice.2014.91
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureusBacteremia in Hospitalized Children: Incidence and Outcomes

Abstract: Kaloudova Y, et al. Epidemiology of ventilator-associated tracheobronchitis and ventilator-associated pneumonia in patients with inhalation injury at the burn centre in Brno (Czech Republic).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
17
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 8 publications
8
17
1
Order By: Relevance
“…23 In our study, adverse outcomes were frequent, with nearly a quarter of all patients studied with S aureus bacteremia experiencing treatment failure. The all-cause case fatality rate was 4%; this rate is within the range of mortality rates reported in children with S aureus bacteremia who are in developing countries, 9,10,12,[24][25][26][27][28] and is considerably lower than the mortality rates seen with adult populations. In fact, age has consistently been noted to be the strongest predictor of all-cause and infection-related mortality, with fatality rates approaching 60% in adults older than 85 years.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…23 In our study, adverse outcomes were frequent, with nearly a quarter of all patients studied with S aureus bacteremia experiencing treatment failure. The all-cause case fatality rate was 4%; this rate is within the range of mortality rates reported in children with S aureus bacteremia who are in developing countries, 9,10,12,[24][25][26][27][28] and is considerably lower than the mortality rates seen with adult populations. In fact, age has consistently been noted to be the strongest predictor of all-cause and infection-related mortality, with fatality rates approaching 60% in adults older than 85 years.…”
Section: Discussionsupporting
confidence: 52%
“…30 A recent retrospective study using a large administrative database of 600 US acute care hospitals to examine outcomes of children hospitalized with S aureus bacteremia found that hospital-onset infections were associated with longer postinfectious length of stay and higher mortality, but those with community-onset infection had a shorter median time to death from bacteremia onset (3 days vs. 6 days), supporting the need for early initiation of empiric therapy in children with S aureus bacteremia. 28 Similarly, another study found that among infants admitted to a NICU who developed S aureus bacteremia, inadequate empirical antibiotic therapy was associated with increased mortality at 30 days for those with MRSA infection. 11 Data from 30 years of surveillance of Danish children with S aureus bacteremia between 1971 and 2000 indicated that increased risk of mortality was associated with pulmonary infection and endocarditis, underlying comorbidities, and hospital-acquired infection, which was not replicated in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Overall, more than half of the children with SAB in our cohort experienced complications. Similar to other published pediatric studies, the most common complications identified in our study were osteomyelitis, skin and soft tissue infection, pneumonia, and septic arthritis [14,20,[22][23][24]. Respiratory distress syndrome was also a common complication in our study, observed in 16% of children.…”
Section: Discussionsupporting
confidence: 90%
“…The morbidities associated with S. aureus bacteremia (SAB) consist of focal and systemic complications that may occur at any bodily site with MRSA twice as likely as methicillin-susceptible S. aureus (MSSA) to cause complications in SAB [12]. Different studies have evaluated complications in children with SAB, including osteomyelitis, septic arthritis, pneumonia, meningitis, infective endocarditis, and toxic-shock syndrome [13][14][15][16][17][18][19][20][21][22][23]. Other complications, including septic shock, respiratory distress syndrome, and splenic abscess have not been extensively described in the pediatric population.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in agreement with other pediatric studies, including a recent report in which two-thirds of S aureus bloodstream isolates were MSSA. 38 In adult and pediatric populations, MRSA bacteremia is by guest on March 24, 2019 www.aappublications.org/news Downloaded from declining, predominantly due to decreasing health care-associated infections. 4,6,39 Improved infection control measures in intensive care units and enhanced surveillance for MRSA are potential reasons for this decline in health care-associated bacteremia, primarily in adult patients.…”
Section: Discussionmentioning
confidence: 99%